Variability of the Antarctic Coastal Current in the Amundsen Sea. (5th November 2016) - Kim, Chang-Sin; Kim, Tae-Wan; Cho, Kyoung-Ho; Ha, Ho Kyung; Lee, SangHoon; Kim, Hyun-Cheol; Lee, Jae-Hak
Abstract: The nature of the Antarctic Coastal Current (AACC) and its seasonal and non-seasonal (several-day) variability were investigated using long-term mooring data obtained near the Dotson Ice Shelf in the Amundsen Sea. The moored instruments were operated from February 2012 to January 2014 in the Dotson Trough, which is one of the deep troughs on the Amundsen Sea shelf. The hydrographic structure of sigma density distribution at the ice shelf (27.25 kg m −3 at the surface) was found to be higher than at the continental shelf (27.00 kg m −3 ), whereas in the middle layer, 27.45 kg m −3 isopycnal extended to 300 m depth near the ice shelf but below 200 m depth in the offshore. The surface mixed layer thickened from the shelf break toward the ice shelf. This thickening was caused partially by coastal downwelling resulting from onshore Ekman transport and by Ekman pumping in the coastal area. The baroclinic component of the AACC near the Dotson Ice Shelf increased from July to October and decreased from January to June in 2013. In comparison with other potential driving forces, the seasonal and non-seasonal (short-term) variation of the AACC correlated well with density variability, determined principally by salinity variation. Therefore, it is suggested that the variability of the isopycnocline by Ekman pumping in the coastal area is one of the important factors controlling the seasonality and non-seasonal variability of the AACC.